Pengawasan Orang Asing terhadap Pemberlakuan Bebas Visa Kunjungan pada Kantor Imigrasi Kelas 1 Khusus Ngurah Rai - Ni Made Putri Kartika Jati; I Wayan Arthanaya; I Nyoman Sutama (Warmadewa Press, 2021)
Free visit visa is a visa granted to foreigners upon arrival in Indonesia without paying a visa for a period of 30 days and cannot be extended. Visit visa free can be given at several Immigration Examination Sites (TPI) spread throughout Indonesia. The Ngurah Rai Special Class I Immigration Office personally supervises an Immigration Checkpoint, namely I Gusti Ngurah Rai International Airport. Regarding the implementation of a visit visa-free policy, the efforts made by the immigration ranks include: increasing the number of personnel, increasing supervision of landings and entry permits for foreigners, monitoring the use of residence permits by foreigners in various places, especially in the tourism sector and in various entertainment venues, there is cooperation between agencies in preventing prevention of visa-free use to minimize potential abuse of rules. The purpose of this study was to determine the application of visa-free policies at the Ngurah Rai Special Class I Immigration Office and to find out the legal consequences of the visa-free policy at the Ngurah Rai Special Class I Immigration Office. The research method uses empirical descriptive. The results of the study indicate that the application of a visa-free policy at the Ngurah Rai Special Class I Immigration Office is in accordance with the latest regulations, namely the Republic of Indonesia Presidential Regulation Number 21 of 2016 concerning Visit Visa Free. There are 169 countries around the world whose citizens can visit Indonesia without using a visa. It aims to improve bilateral relations, especially in terms of the tourism economy where the number of foreign tourists to Indonesia is targeted by the government of 20 million tourists by 2019. Legal Consequences Caused From Visa-Free Policies At the Ngurah Rai Special Class I Immigration Office, where according to one of the immigration functions is to select every intention of arriving foreigners, there are several cases of violations of law which can be easier to enter Indonesia such as foreign workers who work without complete permission in Indonesia.